RELASI SOSIAL BUDAYA DALAM PEMBELAJARAN SEJARAH (STUDI ETNOGRAFI RUANG KELAS DI SMAIT AL-AMRI PROBOLINGGO) - Akhmad Fajar Ma’rufin (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2018)
AbstractThis study aimed to analyze: (1) history teacher’s competency in social cultural setting, (2) the form of social cultural interaction established in history learning process, (3) the effect of social cultural relation in history learning process. This research was conducted in SMAIT Al-Amri Probolinggo.The research method employed was qualitative one with classroom ethnography type. The sampling technique used was purposive sampling with criterion selection. The data collection was conducted using direct observation, ethnographic and document recording methods. The data validation was conducted using triangulation. The data analysis was conducted using an interactive analysis model encompassing data collection, data reduction, data display and conclusion drawing.The result of research concluded that (1) history teacher proffesional competency, from the utilization of student’s cultural setting in learning history, was sufficiently good despite limited scale in certain standard competency but from social competency aspect, there should be an improvement in communication skill, (2) the form of social cultural interaction in history learning constituting verbal and non-verbal communication. The main verbal communication in history learning was debriefing. The main non-verbal communication of student during learning process constituting gesture indicating enthusiasm, (3) the social relation in history learning process led to material breadth by integrating the student’s social cultural setting. The students felt getting involved in learning leading to student’s enthusiasm and social harmony and tolerance among the students. The student’s national cultural orientation was getting wider, as well, particularly in the term of language.Keywords: Social-cultural relation, History learning, SMAIT Al-Amri. AbstrakPenelitian ini bertujuan untuk menganalisis: (1) Kompetensi guru sejarah dalam setting sosial budaya, (2) Bentuk interaksi sosial budaya yang terjalin  dalam proses pembelajaran sejarah, (3) Dampak relasi sosial budaya dalam proses pembelajaran sejarah. Penelitian ini dilakukan di SMAIT Al-Amri Probolinggo.Metode penelitian ini adalah kualitatif dengan jenis etnografi ruang kelas.  Cuplikan yang digunakan dalam penelitian ini adalah purposive sampling dengan criterion selection. Pengumpulan data dilakukan dengan cara observasi langsung, wawancara etnografis dan pencatatan dokumen. Validasi data dilakukan dengan triangulasi. Analisis data yang digunakan adalah model analisis interaktif yaitu pengumpulan, reduksi data, sajian data dan penarikan kesimpulan.Hasil penelitian menyimpulkan bahwa (1) Kompetensi professional guru sejarah dari segi pemanfaatan setting budaya siswa ke dalam materi pembelajaran sejarah  cukup baik meskipun dalam skala terbatas pada standar kompetensi tertentu namun dari segi kompetensi sosial perlu perbaikan (2) Bentuk relasi sosial budaya dalam pembelajaran sejarah  berupa komunikasi verbal dan non verbal. Komunikasi verbal dalam pembelajaran sejarah yang utama adalah tanya jawab. Komunikasi non verbal utama dari siswa selama proses pembelajaran yang berupa gesture yang menunjukkan keantusiasan (3) Adanya relasi sosial budaya yang dipadukan dengan kompetensi guru dalam proses pembelajaran sejarah berdampak pada keluasan materi dengan mengintegrasikan setting sosial budaya siswa. Siswa merasa terlibat dalam pembelajaran sehingga berpengaruh pada keantusiasan siswa. Tercipta pula harmoni sosial dan toleransi antar siswa. Serta orientasi budaya bangsa siswa semakin luas utamanya dalam bidang bahasa.Kata Kunci : Relasi sosial budaya, Pembelajaran sejarah, SMAIT Al-Amri.